Degree Mobility in the Higher Education Context: Could the English Language be a Key Driver of Internationalisation? - Tuğba Elif Toprak Yıldız (Üniversite Araştırmaları Dergisi)
Nowadays, as higher education institutions strive for gaining reputation and increasing their visibility, the notion of internationalisation within the higher education systems continues to attract increasing attention. In particular, the influence of internationalisation on the linguistic landscape of European higher education appears to be far-reaching. Whereas the European Union policies have backed up the idea of multilingualism, the ambition of higher education institutions to draw more accomplished students has boosted the status of English as the lingua franca and medium of instruction. In a similar vein, literature on internationalisation has linked internationalisation to greater degree and credit mobility and extensive use of English as the medium of instruction. Competitiveness in the academic market, in particular, might have caused a considerable number of higher education institutions to associate the notion of internationalisation with Englishisation. While these pressures cement the position of English as the medium of instruction and scholarly activities, this article examines the possible relationships among internationalisation, degree mobility, Englishisation, and language policies in the light of the OECD 2019 and 2020 data. The article also considers several crucial implications for internationalisation that have become increasingly relevant especially during the Covid-19 pandemic period.